Evaluation of biomechanical properties of the cornea in patients with primary hyperparathyroidism - Çankaya, Ali Bülent; Kan, Seyfullah; Kizilgul, Muhammed; Tokmak, Aslı; Inanc, Merve; Caliskan, Mustafa; Beyazyildiz, Emrullah; Açar, Ugur; Delibaşı, Tuncay (Springer Science and Business Media LLC, 2016)
The purpose of this study is to compare the corneal biomechanical properties in primary hyperparathyroid patients and healthy control subjects. The study consisted of 31 patients with primary hyperparathyroidism (study group) and 31 healthy subjects (control group). Corneal biomechanical properties, including corneal hysteresis (CH), corneal resistance factor (CRF), and intraocular pressure (IOP) were measured with an ocular response analyzer (ORA). IOP was also measured using Goldmann applanation tonometry (GAT), and central corneal thickness (CCT) was measured with an ultrasonic pachymeter. The differences in ORA parameters and CCT between study and control group participants were analyzed. The mean CH in study and control groups was 8.7 ± 1.9 mmHg (5.3-13.7 mmHg) and 9.8 ± 1.5 mmHg (7.7-14.3 mmHg), respectively (p = 0.018). The mean CRF was 9.5 ± 1.8 (5.5-13.7) in the study group compared with 9.8 ± 1.5 (6.2-12.8) in the control group. The difference for CRF was not statistically significant (p = 0.41). In study and control group, corneal-compensated IOP (IOPcc) values were 18.2 ± 4.2 and 16.9 ± 2.7 mmHg, respectively (p = 0.12). Mean IOP measurement values with GAT were 16.3 ± 3.4 mmHg for study group and 16.5 ± 2.7 mmHg for control group (p = 0.71). The mean differences of IOPcc and IOPGAT in the study group eyes were higher than that of control group eyes (1.9 vs. 0.4 mmHg). CCT was 536.5 ± 25.4 µm (490-593 µm) in study group eyes compared with 534.2 ± 31.4 µm (472-602 µm) in control eyes (p = 0.75). Hyperparathyroidism could be associated with a decrease of CH. The differences between IOPcc and IOPGAT in these patients were higher than normal subjects. Underestimation of IOP readings with GAT may be a consequence of the lower CH in patients with hyperparathyroididsm.
Keywords: Male; Visual Acuity; Middle Aged; Hyperparathyroidism, Primary; Prognosis; Elasticity; Corneal Diseases; Cornea; Cross-Sectional Studies; Humans; Female; Intraocular Pressure; 3. Good health